373 Is Stereotacticelectroencephalography Safe? A Systematic Review and Meta-Analysis of Stereo-electroencephalography-Related Complications. (1st August 2016) - Mullin, Jeffrey Paul; Shriver, Michael; Alomar, Soha Abdu; Najm, Imad; Gonzalez-Martinez, Jorge Alvaro
Abstract: INTRODUCTION: Stereotacticelectroencephalography (SEEG) is a procedure performed to define the epileptogenic zone in medically refractory epilepsy patients. Despite not requiring a craniotomy, intracerebral electrodes have gained a reputation of a "relatively high morbidity" associated with their placement. The goal of this study is to be the first to quantitatively review the incidence of various surgical complications associated with SEEG electrode implantation in the literature and to provide a summary estimate. METHODS: The systematic review was conducted following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). We conducted MEDLINE, SCOPUS, and Web of Science database searches with the search algorithm. We analyzed complication rates using a fixed-effects model with inverse variance weighting. Calculations for the meta-analysis and construction of forest plots were completed. The principal summary measures were the effect summary value and 95% confidence intervals (CIs). RESULTS: The initial 1901 retrieved citations were reviewed. After removing 787 duplicates, the titles and abstracts of 1114 publications were screened. After excluding 1057 citations, which did not meet our search criteria, the full texts were assessed in the resulting 57 articles for eligibility criteria. The most common complications were hemorrhagic (1.0%, 95% CI 0.6%-1.4%) or infectious (0.8%, 95 CI% 0.3%-1.2%). Five mortalities were identified (0.3%, 95% CI −0.1% to 0.6%). Overall, our analysis identified 121 surgical complications related to SEEG insertion and monitoring (1.3%, 95% CI 0.9%-1.7%). CONCLUSION: This review represents a comprehensive estimation of the actual incidence of complications related to SEEG. We report a rate substantially lower than the complication rates reported for other methods of extraoperative invasive monitoring. These data should alleviate concerns of some regarding the safety of the "stereotactic" method, allowing a better decision process among the different methods of invasive monitoring and ameliorating the fear associated with the placement of depth electrodes.